Asistencia a jardín maternal, educación materna y habilidades lingüísticas tempranas en niños y niñas argentinos - Resches, Mariela (2024)
The impact of Early Child Care attendance on the first language skills of 725 boys and girls from 16 to 30 months living in Buenos Aires and its periphery is analyzed. The fathers and/or mothers filled in the regional adaptation of the Mac Arthur-Bates Communicative Development Inventory and an ad hoc sociodemographic questionnaire. Results indicated significant differences in favor of the children who attended Early Child Care centers, although only after two years old. Early Child Care attendance had a compensating effect for children of mothers with a lower educational level. These data speak in favor of the need to promote public policies that guarantee access to quality educational services for early childhood.